A Rare Case with Quail Egg Allergy without Allergic Reactions to Oral Food Challenge with Hen’s Egg White - Vahid Ghobadi Dana; Mohammad Hassan Bemanian; Raheleh Shokouhi Shoormasti; Saba Arshi; Mohammad Nabavi (Iranian Journal of Allergy, Asthma and Immunology, 2020)
Hen’s egg, as one of the most common reasons for IgE-mediated food hypersensitivity, affects both children and adults. Taking precautionary measures is suggested for the consumption of other birds’ eggs for patients with allergy to hen’s egg. This paper describes a rare patient with quail egg allergy, which manifested no allergic reactions after oral food challenge with hen’s egg white.